(NmUZYKA wENGRII(B.s (NsBORNIK STATEJs - (Ns(B. (Nw(B. (NaKS@Ks (NsOSTAWITELXs ((NmOSKWAs (NmUZYKAs, 1968)
(NkNIGA PRIZWAN OZNAKOMITX MUZYKALXNU@ OB]ESTWENNOSTX S TRUDAMI WENGERSKIH ISSLEDOWATELEJ MUZYKIs
Keywords: (NoPERAs